2014
DOI: 10.1021/mp500062n
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dynamic Stem Cell Culture Platform for Mesenchymal Stem Cell Adhesion and Evaluation

Abstract: The importance of providing a physiologically relevant environment for cell culture is well recognized. The combination of proper environmental cues which are provided in vivo by the bloodstream and extracellular matrix must be reproduced to properly examine cell response in vitro, and cannot be recapitulated using traditional culture on polystyrene. Here, we have developed a device, the dynamic stem cell culture platform (DSCCP), consisting of a biomimetic scaffold cultured within the dynamic environment of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…Three-dimensional cell culture on scaffolds may also be improved by other fabrication-independent parameters such as polarity of cell culture plates, culture media and time [ 26 ], as well as different cell culture types, including a dynamic model [ 27 ]. This optimization will be the focus of further studies as we attempt to improve cell attachment percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional cell culture on scaffolds may also be improved by other fabrication-independent parameters such as polarity of cell culture plates, culture media and time [ 26 ], as well as different cell culture types, including a dynamic model [ 27 ]. This optimization will be the focus of further studies as we attempt to improve cell attachment percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fisher and colleagues recently demonstrated that MSC attachment followed by dynamic substrate movement (stretching) provides one more step in the “education” that MSCs may experience in vivo. 108 The growth of MSCs on soft materials may also preserve the regenerative properties of the cells into later passages or allow them to recover from tissue culture-related aging. 109 The biomaterials-MSC field is actively producing new data, especially in relation to 3D tissue mimetics which may have a profound effect on MSCs, and these data are needed for many growing in vivo applications.…”
Section: Msc Responses—outside-in Signaling On Hard Vs Soft Substratesmentioning
confidence: 99%
“…The oversimplified system in static culture might lead to misleading results, which in most cases contradict results obtained from in vivo animal experiments. This is because cells under fluid flow behave differently than in static culture due to the activation of flow responsive pathways that might influence their cellular adhesion and nanomaterial uptake (Ferlin et al, 2014;Ye et al, 2018). Photothermal therapy, which kills the cancer cells by heat (Jiang et al, 2020), might remove the tumor completely; hence, it is more superior compared to surgical removal.…”
Section: Introductionmentioning
confidence: 99%